Bcl10-controlled malt1 paracaspase activity is key for the immune suppressive function of regulatory T cells - Rosenbaum, Marc; Gewies, Andreas; Kriegsmann, Mark (Nature Communications, 2019)
The differentiation and function of regulatory T (Treg) cells are critically controlled by T cell receptor (TCR) signaling. Here the authors show that CARD11-BCL10-MALT1 (CBM) complexes are dispensable for effector Treg conversion under inflammatory conditions but are critical for mediating Treg suppressive activity in a MALT1 paracaspase-dependent manner.